2005
DOI: 10.1021/jo051572a
|View full text |Cite
|
Sign up to set email alerts
|

Zinc(II) Triflate-Controlled 1,3-Dipolar Cycloadditions of C-(2-Thiazolyl)nitrones:  Application to the Synthesis of a Novel Isoxazolidinyl Analogue of Tiazofurin

Abstract: [reaction: see text] The cycloaddition reaction between C-(2-thiazolyl) nitrones and allylic alcohol takes place with complete exo selectivity when the reactions are carried out in the presence of 1 equiv of zinc triflate. The rate of the reaction is increased enormously under microwave irradiation. The use of a chiral dipolarophile allowed application of the methodology to the synthesis of a hitherto unknown enantiomerically pure isoxazolidinyl analogue of the C-nucleoside tiazofurin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…5 These derivatives show synthetic interest for their potential antiviral or anticancer activity which have been also discovered in other N,O-nucleosides. [6][7][8][9][10][11] Our research group has reported a versatile route towards the synthesis of N,O-psiconucleosides both in racemic and in enantiopure form. 5,[12][13][14][15] More recently, the use of a chiral auxiliary has promoted the enantioselective synthesis of a series of psiconucleosides.…”
Section: Introductionmentioning
confidence: 99%
“…5 These derivatives show synthetic interest for their potential antiviral or anticancer activity which have been also discovered in other N,O-nucleosides. [6][7][8][9][10][11] Our research group has reported a versatile route towards the synthesis of N,O-psiconucleosides both in racemic and in enantiopure form. 5,[12][13][14][15] More recently, the use of a chiral auxiliary has promoted the enantioselective synthesis of a series of psiconucleosides.…”
Section: Introductionmentioning
confidence: 99%
“…where R 1 = Bn; R 2 = H or TBDPS. Chiacchio et al (2005) investigated microwave-assisted, Zn(OTf) 2 -promoted [3+2] cyloaddition between C-(2-thiazolyl)nitrones and allylic alcohols for the synthesis of an enantiomerically pure isoxazolidinyl analog of the C-nucleoside tiazofurin. This reaction is 100% exo-cis selective and show 80% distereofacial selectivity.…”
Section: 3-dipolar Additionmentioning
confidence: 99%
“…Analogues of Tiazofurin, [44] a C-nucleoside with potent antitumor activity against several human cancers, have also been synthesized through 1,3-dipolar cycloadditions between nitrones 37 and allylic alcohol (Scheme 12). Under microwave irradiation and solvent-free conditions, the nitrones 37 react with allylic alcohol (10 equiv.)…”
Section: Cycloadditions Of Nitronesmentioning
confidence: 99%